Tingkat Toleransi Antar Agama Dalam Ruang Lingkup Kampus - Arifin, Finaya Nurul Putri; B, Irnadila Arisyanti; Awaru, A. Octamaya Tenri (IAI Nasional Laa Roiba Bogor, 2023)
Religious tolerance on campus needs to be studied to address conflicts between religious groups that can disrupt a harmonious academic climate. The aim of this research is to explore the level of religious tolerance on campus and the factors that influence it. Survey and interview methods are used to analyze the views, attitudes, and experiences of students regarding religious tolerance on campus. This study indicates that the level of religious tolerance on campus is not yet optimal. Factors such as a lack of understanding of other religions and negative stereotypes are obstacles. A multicultural education approach through dialogue and cooperation between religions is effective in enhancing tolerance. Keywords : Multicultural, tolerance, Campus.